The Aesthetics of Employing the Desert Theme in the Novel “Al-Khabiya” by Jamila Talbawi - El Arabi, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-(–header-height)" dir="auto" data-turn-id="e6ba340d-76bc-4e14-a8ce-eb67ed83d23c" data-turn-id-container="e6ba340d-76bc-4e14-a8ce-eb67ed83d23c" data-testid="conversation-turn-79" data-scroll-anchor="false" data-turn="user"> *]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:38ea93c2-f9b9-4bbb-9c07-4854f35c29e2-39" data-turn-id-container="request-WEB:38ea93c2-f9b9-4bbb-9c07-4854f35c29e2-39" data-testid="conversation-turn-80" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="41a8656a-cb30-4f8d-91aa-6af6503cc816" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> The novel “Al-Khabiya” constitutes an aesthetic space with an artistic structure that reflects the theme of the desert through a narrative discourse directed toward the Other, who produces text in different places. This Other may be close, sharing the same concerns, or distant from the issues of the desert space, yet still sharing in this creative sphere. When speaking about the specificity of space, we refer to the South as an infinite dimension filled with questions worthy of interrogation. This perspective is based on a novel written by a female writer from the same place, in contrast to the writer from outside the place, whose relation to it is temporary and bound to a specific moment in time. The novel “Al-Khabiya” presents a set of propositions organized within a coherent aesthetic system. It can be approached through the notion of judgment applied to this narrative, as a totalizing quality and a subjective proposition dependent on individual perception. This aesthetic appreciation is achieved through the verbal structure of the text itself, without being linked to any external utilitarian function, but rather to the understanding of this artistic experience.